Nocturnal Melatonin Deficiency in Colorectal Cancer: Independent Predictive Value Beyond Sleep Quality - Durak, Ibrahim; Durak, Busra; Duzenli, Tolga; Yilmaz, Musa; Kaya, Muhammed; Sadecolak, Mustafa; Koseoglu, Huseyin; Ozol, Duygu (Turkish Journal of Gastroenterology, 2026)
Background/Aim: Melatonin is a cytoprotective hormone with antioxidant activity and also mediates regulatory effects that inhibit tumor proliferation and angiogenesis. This study aimed to evaluate serum melatonin levels and sleep quality in patients with newly diagnosed colorectal cancer (CRC) compared with controls and to investigate whether melatonin could serve as a potential biomarker. Materials and Methods: A total of 71 participants (36 CRC, 35 controls) were included. Blood samples were obtained between 01:00- 02:00 am and serum melatonin was measured using a high-sensitivity (ELISA) Enzyme-Linked Immunosorbent Assay kit. Sleep quality was assessed with the Pittsburgh Sleep Quality Index (PSQI) and sleep apnea risk was determined by the STOP-Bang questionnaire. Group comparisons were performed, followed by multivariable logistic regression and receiver-operating characteristic analysis. Results: Colorectal cancer patients had significantly lower nocturnal serum melatonin concentrations (131.1 Å} 35.5 vs. 194.8 Å} 50.8 pg/ mL, P < .001) and higher PSQI scores (5.6 Å} 3.1 vs. 5.1 Å} 3.0, P = .028). In multivariable analysis, melatonin remained the only independent predictor of CRC (OR = 0.952, 95% CI: 0.929-0.976, P < .001). Receiver-operating characteristic analysis identified a melatonin threshold of ~150 pg/mL, discriminating CRC patients from controls with 75% sensitivity and 91.4% specificity (AUC = 0.877). Conclusion: Although cancer patients and the control group showed comparable obstructive sleep apnea risk, sleep quality was poorer, and melatonin levels were significantly lower in the cancer group. Melatonin assessment can complement traditional risk stratification and may provide new insights into the interplay between circadian biology, sleep, and colorectal carcinogenesis. Cite this article as: Durak I, Durak B, Duzenli T, et al. Nocturnal melatonin deficiency in colorectal cancer: independent predictive value beyond sleep quality. Turk J Gastroenterol. Published online February 23, 2026. doi: 10.5152/tjg.2026.25808.